Effects of TiO2and SiO2additions on phase formation, microstructures and PTCR characteristics of Sb-doped barium strontium titanate ceramics - P. Bomlai (2018)
Phase formation, densification, microstructural development and the electrical resistivity of Sb-doped Ba0.8Sr0.2TiO3ceramics, containing different sintering additives have been investigated. A secondary phase of (Ba1-xSrx)6Ti17O40was found in samples containing 1 mol% excess TiO2, whereas in samples containing a combination of 1 mol% TiO2and 3 mol% SiO2an additional fresnoite solid solution phase, Ba1-ySryTi1+xSi2-xO8, was found to co-exist at intergranular regions. Grain growth was suppressed by the single TiO2additive, but no improvement in densification was observed. However, the combined excess of SiO2and TiO2promoted liquid phase sintering, producing a reduction in sintering temperature from ∼1350 °C to ∼1250 °C; this additive combination also enhanced the PTCR response. © 2004 Elsevier Ltd. All rights reserved.